Análise histoquímica e morfométrica de componentes fibrosos da matriz extracelular de biópsia de pele de indivíduos com hanseníase no Estado de Sergipe - Mendes, Janine Beltrão Araújo (2015)
Leprosy still constitutes a major problem of public health, in view of its prevalence, morbidity and mortality determined by its complications and its enormous social and economic impact. It is a chronic, infectious disease with long incubation period, caused by Mycobacterium leprae, required intracytoplasmic parasite that affects peripheral nerves and skin. Meet the histological pattern of injury is extremely important for the knowledge base, characterization and treatment of the disease. This research aimed to study the morphology and morphometry of collagen fibers of the extracellular matrix biopsy of patients with leprosy tuberculoid and lepromatous poles. For both experimental and descriptive research was carried out. A total of 20 paraffin blocks, biopsies of patients with leprosy. From these blocks were made in microtome histological sections serially to 5 mm thick, which were submitted to staining: hematoxylin-eosin and hematoxylin-picrosirius. Analyses were performed using images captured by video camera attached to a light microscope Olympus, with an increase of 100 X. From the images obtained from the slides stained with hematoxylin picrosírius- was performed morphometric analysis of collagen fibers through the software Image J®. The information collected was codified and entered into a database for statistical analysis. Significant differences were observed in the inflammatory infiltrate of default in the distribution of collagen fibers and collagen density between the polar forms of leprosy. The tuberculoid form is characterized by inflammatory infiltrate with multiple well-formed and defined granulomas, basically composed of lymphocytes and epithelioid macrophages. Intense inflammatory infiltrate is observed in lepromatous leprosy, distributed diffusely, formed by irregular plates with ill-defined boundaries, composed largely of foamy macrophages. The two poles of the disease, there is a predominance of type I collagen fibers arranged interlaced form. Type III collagen fibers are distributed evenly between the type I, but in less proportion. Type III collagen is more abundant in lepromatous than in tuberculoid form. The degree of collagenization is greater in tuberculoid leprosy compared to lepromatous pole of the disease.